Diatom blooms and associated vegetation shifts in a subarctic peatland: responses to distant volcanic eruptions?. (27th September 2016) - Kokfelt, U.; Muscheler, R.; Mellström, A.; Struyf, E.; Rundgren, M.; Wastegård, S.; Hammarlund, D.
ABSTRACT: We test the hypothesis that rich occurrences of diatoms observed at transitions between major peat units representing different vegetation communities in a peat sequence from subarctic northern Sweden reflect responses to acid deposition from the Samalas AD 1257 and Laki AD 1783/1784 eruptions. We observe sudden changes in the mire ecosystem and thereby in the trophic status and biogeochemical cycling of the peatland. Both the eruptions are known to have been associated with significant acid deposition events and climatic anomalies, as recorded in polar ice cores. To test the hypothesis, new chronological analyses and age modelling were applied to existing biogeochemical and biological records from the peat sequence. This approach yielded modelled age ranges of AD 1239–1284 (1σ)/AD 1210–1303 (2σ) (median: AD 1260) and AD 1674–1795 (1σ)/AD 1665–1875 (2σ) (median AD 1743), respectively, for the stratigraphic transitions. Hence, the modelled age ranges bracket the ages of the eruptions in question and the hypothesis could therefore not be rejected. Impacts of acid deposition from the eruptions are assumed to have caused instant acidification, vegetation damage, increased nutrient cycling and blooms of opportunistic epiphytic diatoms. In addition, cooling may have contributed to vegetation changes through permafrost inception, frost heave and thereby altered hydrological conditions.